2015
DOI: 10.1021/acs.bioconjchem.5b00296
|View full text |Cite
|
Sign up to set email alerts
|

Glycine-Linked Nucleoside-β-Amino Acids: Polyamide Analogues of Nucleic Acids

Abstract: 3'-5'-Deoxyribose-sugar-phoshate backbone in DNA is completely replaced by 2'-deoxyribonucleoside-based β-amino acids interlinked by glycine to create uncharged polyamide DNA with 3'-5'-directionality. These oligomers as conjugates of α-amino acids and nucleoside-β-amino acids bind strongly and sequence-specifically only to the antiparallel complementary RNA and DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Kumar has reported yet another interesting PNA design derived from an alternating sequence of nucleoside b-amino acids and a-amino acid. 113,114 The nucleoside b-amino acids were obtained from the corresponding deoxyribosides. The homo-oligomer of a similar nucleoside b-amino acid derived from AZT has been independently shown to form well-defined folded helical structures but no DNA/RNA binding studies have been reported.…”
Section: Rsc Chemical Biology Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Kumar has reported yet another interesting PNA design derived from an alternating sequence of nucleoside b-amino acids and a-amino acid. 113,114 The nucleoside b-amino acids were obtained from the corresponding deoxyribosides. The homo-oligomer of a similar nucleoside b-amino acid derived from AZT has been independently shown to form well-defined folded helical structures but no DNA/RNA binding studies have been reported.…”
Section: Rsc Chemical Biology Reviewmentioning
confidence: 99%
“… 113 Subsequent report with mixed-sequence PNA with glycine spacer also confirmed the generality of this preference and allowed the determination of the directional selectivity as exclusively antiparallel. 114 Nevertheless, the stability difference between RNA and DNA was only marginally better than in the case of aegPNA ( Table 16 ). In addition, the thermal stability was generally lower than that of the corresponding aegPNA duplexes with a similar level of mismatch discrimination.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Others have also recognized this potential and developed novel DNA and RNA analogues based on derivatives of amide backbone. [60][61][62] We also propose that non-ionic linkages, and amides in particular, have great potential to contribute to fundamental studies and practical applications by optimizing CRISPR associated RNAs and other functional RNA molecules, many of which are yet to be discovered. The RNA components of RNAi and CRISPR share many common structural and functional features, and it is conceivable that lessons learned when replacing phosphates with amides in siRNAs will guide development of optimized CRISPR associated RNAs.…”
Section: Conclusion and Outlook: Rnai Crispr And Beyondmentioning
confidence: 99%
“…[133] Also, the resistance towards hydrolytic cleavage and their extraordinary thermal stability make PNAs in many respects interesting and facilitate many application opportunities in the field of diagnostics and pharmaceuticals. [134][135][136][137] Compared with DNA and RNA, PNAs can form more stable duplex structures. [138,139] Furthermore, strong duplex formation between DNA/DNA strands can be disturbed by adding PNA.…”
Section: N-(2-aminoethyl)-glycine (Aeg)-pnamentioning
confidence: 99%